2001
DOI: 10.1161/01.hyp.37.2.408
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Blood Pressure and Heart Rate Variability in Transgenic Rats With Low Brain Angiotensinogen

Abstract: Abstract-To study whether the brain renin-angiotensin system plays a role in the long-term and short-term control of blood pressure and heart rate variability, we examined in transgenic rats [TGR(ASrAOGEN)] with low brain angiotensinogen levels the 24-hour variation of blood pressure and heart rate. Telemetry recordings were made during basal and hypertensive conditions induced by a low-dose subcutaneous infusion of angiotensin II for 7 days. Short-term blood pressure and heart rate variability were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
61
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 45 publications
4
61
1
Order By: Relevance
“…In addition, renal denervation resulted in a significant reduction of LVI only in female SHR, although the blood pressure was similarly decreased by the maneuver in both sexes. This effect occurred without alterations in BRS and thus does not support previous studies indicating that cardiac hypertrophy is associated with an alteration in BRS (1,18). The mechanism then for the reduction in LVI with renal denervation in female SHR is not clear from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, renal denervation resulted in a significant reduction of LVI only in female SHR, although the blood pressure was similarly decreased by the maneuver in both sexes. This effect occurred without alterations in BRS and thus does not support previous studies indicating that cardiac hypertrophy is associated with an alteration in BRS (1,18). The mechanism then for the reduction in LVI with renal denervation in female SHR is not clear from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although increased baroreflex sensitivity was reported in some studies (2,4), another study reported no change in baroreceptor reflex in rats lacking glial AGT (7). An alteration in circadian variation in blood pressure was also reported in these rats (1). The data obtained to date therefore support the conclusion that glial cells are an essential source of ANG II substrate in the brain in the regulation of cardiovascular function.…”
Section: Discussionsupporting
confidence: 82%
“…Frequently, so-called HRV analysis in animals is performed on data derived not from an ECG signal but from the arterial pulse waveform obtained by a radiotelemetry implanted into a main artery (3,4,19). This is a much different pulse wave monitoring technique than has been investigated in clinical studies, and it is thus important to understand how well measures of pulse rate variability (PRV) obtained via chronically implanted radiotelemetry agree with measures of HRV obtained via ECG.…”
mentioning
confidence: 99%